Initial exploration of the discriminatory ability of the PetPace collar to detect differences in activity and physiological variables between healthy and osteoarthritic dogs - Rowlison de Ortiz, Avery; Belda, Beatriz; Hash, Jon; Enomoto, Masataka; Robertson, James; Lascelles, B. Duncan X. (Frontiers in Pain Research, 2022)
Background: Accelerometry has been used to evaluate activity in dogs with osteoarthritis (OA) pain, especially in relation to effect of treatment; however no studies have compared accelerometry-measured activity in dogs with OA-pain and healthy dogs. The aims of this study were to 1) compare activity output from the PetPace collar with the validated Actical monitor and 2) determine if PetPace collar outputs (overall activity, activity levels, body position, and vital signs) differed between healthy dogs and dogs with OA-pain. Methods: This was an observational, non-interventional study in healthy dogs and dogs with OA-pain. All dogs were outfitted with the PetPace collar and the Actical monitor simultaneously for 14 days. Output from these devices was compared (correlations), and output from the PetPace device was used to explore differences between groups across the activity and vital sign outputs (including calculated heart rate variability indices). Results: There was moderate correlation between the PetPace collar and Actical monitor output (R2=0.56, p<0.001). Using data generated by the PetPace collar, OA-pain dogs had lower overall activity counts and spent less time standing than healthy dogs. Healthy dogs spent more time at higher activity levels than OA-pain dogs. Certain heart rate variability indices in OA-pain dogs were lower than in healthy dogs. Conclusions and Clinical Relevance: The results of this study suggest that the PetPace collar can detect differences between healthy dogs and those with OA-pain, and that OA-pain negatively impacts overall activity levels in dogs, and especially higher intensity activity.